2003
DOI: 10.1096/fj.03-0181fje
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ activation enhances cell surface ENaCα via up‐regulation of SGK1 in human collecting duct cells

Abstract: Peroxisome proliferator-activated receptor gamma (PPARgamma) is a ligand-dependent transcription factor that belongs to the nuclear receptor family that plays a critical role in adipocyte differentiation and lipid metabolism. Here we report for the first time that PPARgamma is expressed in human renal cortical collecting ducts (CCD), segments of the nephor involved in regulation of sodium and water homeostasis via action of the epithelial sodium channel (ENaC). ENaC activity is regulated by the hormones aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 38 publications
5
106
1
1
Order By: Relevance
“…The latter were in the lower micromolar range (10-15 μM), which is comparable to levels measured in volunteers after oral ingestion of 30 mg pioglitazone (3 μM; [44]). At those concentrations, pioglitazone does increase extracellular fluid volume, as previously shown for PPARγ agonists [18,22,49].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The latter were in the lower micromolar range (10-15 μM), which is comparable to levels measured in volunteers after oral ingestion of 30 mg pioglitazone (3 μM; [44]). At those concentrations, pioglitazone does increase extracellular fluid volume, as previously shown for PPARγ agonists [18,22,49].…”
Section: Discussionsupporting
confidence: 78%
“…The use of the PPARγ agonists has, however, been impeded by their volume retaining properties [18,22,49]. In patients with congestive heart failure (CHF), treatment with PPARγ agonists was associated with decompensation and occurrence of pulmonary edema [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is supported by several lines of direct and indirect evidence from previous studies. First, in a cultured human cortical CD cell line, PPAR␥ agonists increase levels of cell surface ENaC␣, paralleled by stimulation of gene expression of serum and glucocorticoid regulated kinase 1 (SGK1), a key mediator of aldosterone activation of ENaC (29). Second, a PPAR␥ ligand, GI262570, increased expressions of ENaC␣, SGK1, and Na-K-ATPase␣ in the renal medulla (26).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action behind the fluid retention with TZDs (e.g., cardiac cause or drug interaction with receptors on sodium channels) remain unclear, although it has been suggested that peroxisome proliferator-activated receptor-␥ may regulate sodium reabsorption in the cortical collecting ducts (segments of the nephron involved in regulation of sodium and water homeostasis) via stimulation of epithelial sodium channel activity (22). The long-term study of pioglitazone use and heart failure, funded by the American Diabetes Association (18), argues against the possibility that TZDs cause heart failure.…”
Section: Edemamentioning
confidence: 99%